Implementasi Fungsi Badan Permusyawaratan Desa Menurut UU No. 6 Tahun 2014 (Studi Kasus di Desa Sidodadi Kecamatan Masaran Kabupaten Sragen) - Al Roni, Harun; , Dra. Hj. Sri Gunarsih, SH., MH (2017)
This study aims to: (1) Descibe the implementation of the Village Consultative Body functions according to Act No. 6 2014 conducted by the District Sidodadi Village BPD Masaran Sragen; (2) Describe the obstacles faced by BPD in performing its functions; (3) Describe the efforts made by the BPD in addressing barriers to the implementation of the functions of BPD. This research is qualitative research conducted in the field. This research uses descriptive method to describe phenomena relating to the implementation of the function of BPD according to Law No. 6 2014 about the village. Sources of data obtained through informants, places and events, as well as documents. The technique of collecting data using interviews and observation. Interviews were conducted with the chairman and members of the BPD, village heads and community. Data were analyzed using qualitative descriptive analysis. The procedures in this study there are four stages: pre-field, fieldwork, data analysis and documentation analysis. The results showed that: (1) Implementation of Rural Sidodadi BPD function in accordance with Article 55 of Act No. 6 of 2014 about Village are: to discuss and agree draft Regulation village along the village chief, and share their aspirations Village community, and to supervise the performance of the Village Chief; (2) Obstacles encountered in implementing the Sidodadi Village BPD BPD functions are: (a) internal barriers: the bustle of the BPD and BPD operational funds are not sufficient; (B) external obstacle: the mechanism of action of village government is less open to the BPD and the lack of understanding of village government and community over BPD position; (3) The efforts made by BPD Village Sidodadi in overcoming barriers to implementation of the functions of BPD is: (a) Measures to overcome barriers to the internal is the implementation musyawarag at night, Sedangka operational funds is minimal can be resolved in coordination with the village to make spending cuts village ; (B) Measures to overcome external obstacles: to hold regular coordination meetings between the village government amicably as well as attending regular meetings to explain the position at RT for BPD in the village.